HUBUNGAN HARGA DIRI DENGAN ALTRUISME ANAK USIA 5-6 TAHUN DI TKIT AL-ITTIHAD KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Qomariah, Siti; Risma, Devi; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the relationship between self-esteem and altruism of children aged 5-6 years at TKIT Al-Ittihad, Rumbai Pesisir District, Pekanbaru City. The population in this study were all children aged 5-6 years. for a sample of 100 children. The method used in this study is quantitative correlation to see the relationship between independent variables and bound. Data collection techniques used are observation. Data analysis techniques used the chi square test and statistical method analysis with the IBM SPSS for Windows Ver program. 23. Based on the results of hypothesis testing there is a significant positive relationship between self-esteem and altruism of children aged 5-6 years at TKIT Al-Ittihad, District of Rumbai Pesisir, Pekanbaru City. This can be seen from the value of the correlation coefficient of 0.869 and the significance level of 0.000 <0.05. The level of the relationship between self-esteem and children's altruism falls into the very strong category.Key Words: Self Esteem, Altruism